Angus Ground Beef Has Higher Overall Consumer Acceptability than Grass-Fed Ground Beef - F. Najar; E. A. Boyle; T. G. O'Quinn; R. Danler; S. Stroda; L. N. Drey; K. R. Vierck; G. D. McCoy (Kansas Agricultural Experiment Station Research Reports, 2017)
Ground beef is considered one of the major sources of animal protein in the U.S., accounting for approximately 40% of beef consumption per capita (USDA, 2011). Consumers’ concern about animal welfare, sustainable production, and low fat products has influenced purchasing decisions, resulting in an increased demand for grass-fed ground beef (U.S. Department of Agriculture, Agricultural Marketing Service, 2007). Grass-fed cattle are fed natural based forages or grass-hay, thus resulting in a higher deposition of omega-3 fatty acids in meat. Meat from grain-fed cattle has a lower omega-3 content due to the saturated and monounsaturated fatty acid profile found in a grain based diet. Additionally, grass-fed ground beef contains three times more omega-3 fatty acids than traditional grain-fed ground beef; however, there is no evidence to support that grass-fed ground beef is a healthier choice for consumers than traditional ground beef (Smith, 2013). Several studies have looked at the flavor profile between grass-fed and grain-fed beef in order to identify whether the omega-3 fatty acids found in grass-fed ground beef play a key role on consumer flavor acceptability. A high content of omega-3 fatty acids accelerates oxidization of meat, and consequently causes potential adverse effects on meat palatability traits. Consumer sensory evaluation was conducted to evaluate consumer palatability ratings of grass-fed ground beef in comparison to Angus and commodity ground beef.
Keywords: ground beef; consumer; palatability